Kebiasaan Tidak Menggunakan Selimut/Pakaian Lengkap Sewaktu Tidur Malam Sebagai Faktor Risiko Terinfeksi Filariasis Pada Anak Usia Sekolah Dasar - Ikrimah Nafilata; Praba Ginandjar (LPPM STIKES Guna Bangsa, 2019)
Filariasis is caused by 3 species of filarial worms and is transmitted by the Culex quinquefasciatus mosquito. Pekalongan Regency is an endemic filariasis area with an Mf rate of >1%. The prevalence of filariasis in primary school children is 1.98% in Tirto and Buaran Subdistricts, the behavior of using blankets / complete clothing while sleeping at night in children needs to be studied further to prove the risk factors for filariasis. This study is a cross sectional analytic study, to prove the use of blankets / complete clothing during night sleep as a risk factor for the incidence of filariasis, using purposive samples of 84 samples of primary school age children in grades 3, 4, 5, 6. The stage of this research is finger blood screening using Immunochromatographic Card Test (ICT), indept interview and direct observation in Tirto and Buaran Subdistricts of Pekalongan Regency. The results of screening 17 positive and 67 negative filariasis were obtained. The results of the analysis using Chi Square did not use blankets / complete clothing while sleeping at night, p = 0,000 and POR = 10,967 (95% CI: 2,837-42,400). Not using mosquito nets when sleeping at night p value = 0.022 and POR = 4.527 (95% CI: 1.335-15.3353). The habit of playing in the open space / place of breeding / resting vector is obtained p = 0.830 and POR = 1.383 (95% CI: 0.401-4.764). Not using blankets / complete clothes while sleeping at night and not using mosquito nets while sleeping at night is a possible risk factor for filariasis in primary school-aged children.